PENGARUH MODEL PEMBELAJARAN INQUIRY YANG DIRANCANG UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII DALAM MATAPELAJARAN SEJARAH DI SMP NEGERI 2 MANDREHE - Gulo, Festi Memori; Lase, Asali; Laoli, Bezisokhi; Telaumbanua, Wahyutra Adilman (Yayasan Amanah Nur Aman, 2025)
This research was motivated by the results of a preliminary study conducted at SMP Negeri 2 Mandrehe, which revealed an ongoing issue of low student engagement in the learning process. This study describes the implementation of learning activities through the guided inquiry model and investigates whether the guided inquiry learning model has a significant influence on students' critical thinking skills. The research was conducted at SMP Negeri 2 Mandrehe using an experimental research design, with the population consisting of classes VIII-1 and VIII-2. The sample was selected using a saturated sampling technique.Based on the research findings on the implementation of the guided inquiry learning model, the experimental class had an average post-test score of 85.65, while the control class had an average score of 56.55. Class VIII-1 achieved a score of 75, meeting the Minimum Mastery Criteria (KKM) for the topic Economic Actors at SMP Negeri 2 Mandrehe. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The general conclusion indicates that the guided inquiry learning model is effective in improving the critical thinking skills of students at SMP Negeri 2 Mandrehe.